2020
DOI: 10.1111/ibi.12827
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure influences predation rates of early nests in subarctic breeding waders

Abstract: Ground‐nesting species are vulnerable to a wide range of predators and often experience very high levels of nest predation. Strategies to reduce nest vulnerability can include concealing nests in vegetation and/or nesting in locations in which nests and eggs are camouflaged and less easy for predators to locate. These strategies could have important implications for the distribution of ground‐nesting species and the success rates of nests in areas with differing vegetation structure. However, the factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
1
25
1
Order By: Relevance
“…The presence of higher numbers of alternative prey may promote increased numbers of breeding shorebirds (Blomqvist et al, 2002;Robinson et al, 2014) and mitigate the risk of predation on their nests (Bêty et al, 2002;Smith et al, 2007;McKinnon et al, 2012, but see Weiser et al, 2018a. Persistent spring snow cover may also directly increase the predation of shorebird nests, as late-melting snow limits the area available for nesting, allowing predators to concentrate their search effort (Byrkjedal, 1980;Meltofte et al, 1981;Machín et al, 2019), and the growth of vegetative cover is phenologically delayed making nests more obvious (Laidlaw et al, 2020). However, late-melting snow may also lead to synchronous nesting that could dilute the risk of predation to any one nest .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of higher numbers of alternative prey may promote increased numbers of breeding shorebirds (Blomqvist et al, 2002;Robinson et al, 2014) and mitigate the risk of predation on their nests (Bêty et al, 2002;Smith et al, 2007;McKinnon et al, 2012, but see Weiser et al, 2018a. Persistent spring snow cover may also directly increase the predation of shorebird nests, as late-melting snow limits the area available for nesting, allowing predators to concentrate their search effort (Byrkjedal, 1980;Meltofte et al, 1981;Machín et al, 2019), and the growth of vegetative cover is phenologically delayed making nests more obvious (Laidlaw et al, 2020). However, late-melting snow may also lead to synchronous nesting that could dilute the risk of predation to any one nest .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of overall differences between day and night predation are described, but not formally tested, from the subarctic and arctic regions (Laidlaw et al., 2020 ; Tulp & Schekkerman, 2001 ), and anecdotal evidence suggests that the lack of diel pattern in nest predation may be found also in species from regions with a similar composition of predator community (Kosztolanyi et al., 2009 ; Shkedy & Safriel, 1992 ). Moreover, around the clock predation is common in ground‐nesting passerines (Pietz et al., 2012 ; Praus & Weidinger, 2010 ; Weidinger, 2010 ), as well as in small shorebirds, that do not actively deter predators (Ekanayake, Weston, et al., 2015 ; Macdonald & Bolton, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…We considered nests as hatched ( N = 312), when at least one chick hatched, based on observations of (i) at least one chick on or around the nest during the final nest‐check ( N = 197 nests), (ii) color‐marked parents guiding chicks after the final nest visit ( N = 36 nests), or (iii) small (≤ 5mm) eggshell pieces in the nest that result from a chick chipping its way out of its egg ( N = 79; Brown et al., 2014 ; Mabee et al., 2006 ). The use of eggshell pieces has been used to define successfully hatched nests in other shorebird species (Kentie et al., 2015 ; Laidlaw et al., 2020 ). Importantly, we ringed 233 chicks whose identity was unknown as they were found away from nests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results in the north European macroecological gradient are supported by other comparative studies. In Iceland, where our nest predation experiment failed, Laidlaw, et al [97] monitored 469 wader nests in 2015 and 2016, of which 40% were predated. Groen, et al [98] and Kentie, Both, Hooijmeijer and Piersma [33] also demonstrated lower wader nest predation patterns (daily predation probability of 0.025) in favourable semi-natural grasslands compared to unfavourable intensified grassland monocultures (0.045) in Friesland, Netherlands.…”
Section: Clear Macroecological Patterns Across Landscapesmentioning
confidence: 99%